2005
DOI: 10.1007/s10310-004-0101-3
|View full text |Cite
|
Sign up to set email alerts
|

Ectomycorrhizal development in a Pinus thunbergii stand in relation to location on a slope and effect on tree mortality from pine wilt disease

Abstract: The relationship between ectomycorrhizal development and mortality from pine wilt disease was studied in an artificial Pinus thunbergii Parl. stand on a slope. The development of ectomycorrhizae and the survival of the trees showed the same tendency, which suggests a correlation between mycorrhizal development and resistance to pine wilt disease. The development of pine roots and mycorrhizae was greater in the upper part of the slope. The ratio of mycorrhizae to the total of mycorrhizae and fine taproots was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
18
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 9 publications
1
18
0
Order By: Relevance
“…1999), light conditions (Mabuhay and Nakagoshi 2012), soil water content (Suzuki and Kiyohara 1978; Miki et al. 2001; Akema and Futai 2005), and soil physicochemical properties (Kim et al. 2010; Mabuhay and Nakagoshi 2012).…”
Section: Introductionmentioning
confidence: 99%
“…1999), light conditions (Mabuhay and Nakagoshi 2012), soil water content (Suzuki and Kiyohara 1978; Miki et al. 2001; Akema and Futai 2005), and soil physicochemical properties (Kim et al. 2010; Mabuhay and Nakagoshi 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the effects of soil conditions should be considered to understand the relationship between ectomycorrhizal association and pine wilt damage. Neither Akema and Futai (2005) nor Ichihara et al (2001) reported the ectomycorrhizal community structure on pine roots. Kikuchi et al (1991) compared the different effects of ectomycorrhizal species on pine resistance, but they observed only two fungal species.…”
mentioning
confidence: 89%
“…Akema and Futai (2005) reported a difference in soil moisture between the upper and lower slopes. Soil conditions such as soil moisture can infl uence ectomycorrhizal association (Slankis 1974).…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…Forest fire often kills host trees and this is fatal to ectomycorrhizal fungi because they are virtually obligate symbionts. However, even if the host trees survived, mycorrhizae can be seriously damaged by the burning of the litter layer and consequent heating of top soil because mycorrhizae distribute mainly in the top soil 3 . In dipterocarp trees, the loss of the functions of ectomycorrhizae may be a very serious problem to the recovery from the forest fire, because they largely depend on mycorrhizae for the function of the roots.…”
Section: Introductionmentioning
confidence: 99%